Risk Management in Clinical Trials: Assessment of Current Practices at Portuguese Clinical Trial Sites - Vale M; Leite F; Madeira C (Risk Management and Healthcare Policy, 2023)
Margarida Vale,1 Francisca Leite,2,3 Catarina Madeira1,2,4 1NOVA Medical School, Universidade NOVA de Lisboa, Lisboa, Portugal; 2Associação CoLAB TRIALS, Évora, Portugal; 3Hospital da Luz Learning Health, Lisboa, Portugal; 4CHRC, NOVA Medical School, Universidade NOVA de Lisboa, Lisboa, PortugalCorrespondence: Catarina Madeira, CoLAB TRIALS, Largo do Senhor da Pobreza, Escola Superior de Enfermagem São João de, Deus, Évora, 7000-811, Portugal, Tel +351 91 4006726, Email catarina.madeira@colabtrials.ptPurpose: Over the last years, in response to the increasing complexity and demand of clinical trials, there has been a growing concern with the application of efficient risk management methodologies. The main objective of this work is to assess the current level of implementation of risk management activities by clinical trials sites’ teams and identify points of improvement.Methods: A cross-sectional study was conducted through an original, non-validated questionnaire created to assess the risk management practices at Portuguese clinical trial sites. The web-based survey was sent by e-mail to the clinical trial sites identified, and it was available for one month. Descriptive statistics were used to summarize the findings.Results: In total, 46 clinical trial sites accepted to participate in this study. The surveys’ answers showed that although 57.0% of sites reported the use of a systematic risk management tool, only nine sites (19.6%) described a standard tool or document that captured systematically the analysis of risks at the site level. Most of the sites (87.0%) showed willing to use a risk management tool specifically tailored for their operational needs, with the lack of knowledge about risk management being the main reason against its implementation.Conclusion: This work indicates that the surveyed clinical trial sites generally recognize the importance of risk management methodologies as an opportunity to anticipate difficulties in the trial conduct and optimize the use of sites’ resources. However, mainly due to lack of experience with risk management methodologies, sites are not currently implementing these strategies in the management of their trial-related operations. The development of a risk management tool for sites can be useful in this context.Keywords: clinical research, operational risks, planning, trial feasibility, healthcare, risk assessment tool